Analisis Kinerja Ruas Jalan Raya Casablanca Berdasarkan Pedoman Kapasitas Jalan Indonesia (PKJI 2023) - Johanes Marpaung; Gali Pribadi; Bermando Mangatur S. (Asosiasi Riset Ilmu Teknik Indonesia, 2026)
The growth in the number of vehicles that is not balanced by the increase in road capacity has led to a decrease in traffic performance, especially in commercial areas with high activity. This study analyzes traffic characteristics, road capacity, degree of saturation, and performance of the Casablanca Highway, South Jakarta, based on the 2023 Indonesian Road Capacity Guidelines (PKJI). The research method used a descriptive quantitative approach by collecting primary data through field surveys for 14 consecutive days in three observation periods, namely morning, noon, and evening. The data collected included traffic volume, vehicle speed, side obstacles, and road geometry conditions. The results of the study showed that the traffic flow was dominated by motorcycles by 59.98% and passenger cars by 38.40%. The highest volume was recorded on Friday at 16.00-17.00 WIB at 8,841 SMP/hour, with an average vehicle speed of only 6.17 km/h. The capacity of the road section was obtained at 4,965 junior high schools/hour with a saturation degree of 1,781, which indicates saturated conditions. This situation leads to a decrease in speed, an increase in density, as well as the potential for delays and queues of vehicles during peak hours. Therefore, it is necessary to manage side obstacles and traffic engineering to improve the performance of the Casablanca Highway section.